สามประสานเพื่อการพัฒนาอาชีวอนามัยสำหรับผู้สูงอายุข้อเข่าเสื่อมที่ประกอบอาชีพกรีดยางพารา - ชนนท์ กองกมล (มหาวิทยาลัยสงขลานครินทร์, 2021)
Background: Knee pain is a leading cause of functional impairment and decrlity of life among aged para rubber farmers in Thailand, Promoting self-ers and increasing role of health care workers in occupationalcritical issues in primary care.Objective: This study aimed to develop the supportive-educative care model as apractical model for aged para rubber farmers with knce OA.Methods: An action research approach was taken effort with the health care workers,including 10 community health volunteers and 30 aged para rubber farmers with knceosteoarthritis. Three parties on building the healthy public policy (professionals,decision makers, and community citizen), namely "Triangle that moves the mountain"and the Self-care deficit nursing theory were used as the theoretical foundations. Fourphases according to the action research cycle: the initial assessment, the developmentof the model, the application of the newly developed model, and the evaluation ofchange were conducted. Data were collected by focus group, personal interview andbrainstorming and analyzed using content analysis.Results: The supportive-educative care model comprises: (i) educative program forthe trainers (ii) goal-directed and self-care plan on ergonomic management andmuscle strengthening exercise for the aged individuals (ii) practical tool developmentfor home visiting program and (iv) supportive system for the professionalconsultation.Conclusion: The practical supportive-educative care model seems to fulfill the careneeds of aged para rubber farmers with knee OA and enhance their self-care. Inaddition, maximizing care competences of the health volunteers is achieved throughpartnerships of the community parties responding to the primary care.